Complicated Full-Thickness Corneal Lacerations and Perforations in Cats - Demír, Aynur; Ibrahim Kurban (Acta Scientiae Veterinariae, 2024)
Background: One of the potentially serious eye injuries that can lead to blindness in cats is "full-thickness corneal lacerations and perforations." These injuries require immediate medical intervention, and if left untreated, they can lead to complications such as the risk of infection. Treatment typically depends on the size, depth, and severity of the corneal injury. Small tears and perforations can sometimes be treated with topical antibiotics and eye drops, but larger and deeper injuries may require surgical intervention. Surgical intervention may involve procedures to close the injury and promote the healing process. In the study, the frequency of cats being exposed to full-thickness corneal lacerations and perforations; prevalence by breed; breed, age, and gender predisposition; affected ocular structures; lesion duration; findings of ophthalmological examination; and outcomes of medical and surgical therapies were evaluated in 50 cats (53 eyes). Materials, Methods & Results: Of the total 50 cats, 74% were Domestic Shorthairs with an average age of 34.8 months. 54% of these were female, and 76% were under 3-year-old. The causes were categorized as traumatic (66%) and non-traumatic (34%). The treatment protocol was categorized as medical treatment alone (n = 16/53) and surgical treatment combined with medical therapy (n = 37/53). Surgical procedures included nictitating membrane flap (NMF; n = 10), conjunctival pedicle flap (CPF) combined with NMF (n = 20), and suture closure combined with NMF (n = 7). Treatment outcomes were evaluated by assessing vision within the initial month and corneal transparency within 1-3 months. The process of epithelization and complete recovery followed distinct timelines: 10 days to 1 month and 1-2 months solely with medical therapy; 3-4 weeks and 5-7 weeks with NMF treatment alone; 2-3 weeks and 4 weeks to 4 months with a combination of CPF and NMF; and 2-5 weeks and 4-8 weeks with suturing combined with NMF, respectively. Out of 45 cats, corneal integrity was successfully restored in 48 eyes (90.56%). Nevertheless, despite various treatment combinations, 5 eyes from 5 cats did not respond to treatment. Discussion: The findings of this study provide important insights into managing full-thickness corneal lacerations and perforations in cats, emphasizing the significance of prompt intervention to prevent potential vision loss. The prevalence of Domestic Shorthairs among affected cats underscores the importance of understanding breed predispositions in ocular injuries. Traumatic causes are more common than non-traumatic ones, highlighting the necessity of taking preventive measures, especially in environments where cats may be exposed to potential hazards. The wide range of treatments utilized in the study demonstrates the potential effectiveness of both medical therapies and surgical interventions. While treatment outcomes indicate successful restoration of corneal integrity and vision in the majority of cases, the inability to achieve a response in some instances underscores the necessity for better understanding of treatment protocols and factors influencing success. Overall, this study emphasizes the importance of a comprehensive approach to managing full-thickness corneal lacerations and perforations in cats, aiming to preserve vision through early diagnosis, appropriate treatment selection, and vigilant monitoring for optimal outcomes. Keywords: cat, cornea, laceration, perforation, treatment.